The Collapse of the Space Building and the Absence of Supervision - Perico-Granados, Néstor Rafael (2024)
The investigation identified potential causes for the failures observed in several construction projects in Colombia during the second decade of the 21st century. The study aimed to establish a link between these issues and the lack of proper oversight, as effective supervision promotes quality in both design and construction phases. The methodology involved a comprehensive review of relevant legislation and academic studies conducted by esteemed Colombian universities. A notable example is the Space building in Medellín, Colombia, where the collapse of Tower 6 in 2013 resulted from structural failures, leading to significant human, material, and environmental damages. Similarly, other construction projects with inconsistencies and subsequent damages include Reficar, Puente Chirijara, and Hidruitango. The findings revealed deficiencies in structural design and foundation, as well as the approval of curatorial licenses without external verification of compliance with technical specifications. Furthermore, the project's design and execution disregarded earthquake-resistant regulations, including Law 400 of 1997. The study concludes that proper oversight acts as a preventive measure, minimizing human casualties, structural damage, and environmental harm. Hence, the project supervisor plays a crucial role in ensuring the stability and quality of the construction.